Conflict, compromise and collusion: dilemmas for psychosocially-oriented practitioners in the mental health system. Issue 3 (3rd July 2019) - Cooke, Anne; Smythe, William; Anscombe, Philip
ABSTRACT: The nature and causes of mental health problems are contested. The dominant approach in services views them as "illnesses like any other". The structure, legislative base and practices of mainstream mental health services are largely predicated on this idea, known variously as the medical, illness, disease or diagnostic model. By contrast, psychosocial theories highlight the role of the events and circumstances of peoples' lives. The tension between these two approaches can lead to challenges and dilemmas for psychosocially oriented practitioners. Clinical psychologists participated in interviews and a focus group about these challenges and how they managed them. A grounded theory was constructed which suggested that their responses took three forms: openly "dissenting" ( conflict ), strategically "stepping into" the medical model ( compromise ), or inadvertently "slipping" into it ( colluding ). Strategies for managing the challenges included focusing on clients; foregrounding clients' contexts and understandings; holding the tension between "expert" and "not-knowing" approaches; using ordinary language; forging robust working relationships; being mindful of difference and of constraints on colleagues; recognising one's power and ability to influence; self-care and work/life balance; taking encouragement from small changes; consolidating a personal philosophy; mutual support and solidarity; drawing on scholarship and finally engaging in activism outside work.